Urban Environmental Indicators: Case Study of Passo Fundo-RS - Campestrini, Júlia Brum; Silva, Thaísa Leal da (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
Rapid urbanization results in several challenges related to urban infrastructure, and it is difficult to draw up new solutions for improvements, adaptations, and plans for better urban development. In this context, this study aims to analyze the urban environmental indicators of the city of Passo Fundo, in the north of Rio Grande do Sul, according to the Connected Smart Cities Ranking (RCSC) to identify positive and negative points in the indicators analyzed in relation to the object of study. For this, the research methodology was divided into the following stages: bibliographical review, diagnosis of the city, survey of the indicators of the analyzed Environment axis, and comparison of the indicators of Passo Fundo/RS with the indicators of medium-sized cities in the South Region of Brazil best classified in the Ranking in the years 2019, 2020 and 2021. From the comparison of the results, it was possible to verify the development of Passo Fundo during the three years of analysis, ascertaining that there was a concern with investments to improve infrastructure and services aimed at to the Environment. With the study, it was possible to see that Passo Fundo seeks to improve its services but lacks attention in terms of water loss rates during its distribution and the city's sewage collection and treatment. Furthermore, the importance of measuring and monitoring urban indicators was noted so that they can contribute to the planning of new municipal guidelines, and to the development of initiatives to combat and prevent urban health-related problems.
Keywords: Smart cities; Environment; Urban Indicators